Non-invasive imaging shows no evidence of embolism repair after drought in tree species of two genera. (22nd August 2018) - Choat, Brendan; Nolf, Markus; Lopez, Rosana; Peters, Jennifer M R; Carins-Murphy, Madeline R; Creek, Danielle; Brodribb, Timothy J
Abstract: Drought stress can result in significant impairment of the plant hydraulic system via blockage of xylem conduits by gas emboli. Recovery after drought stress is an essential component of plant survival but is still a poorly understood process. In this study, we examined the capacity of woody species from two genera ( Eucalyptus and Quercus ) to refill embolized xylem vessels during a cycle of drought and recovery. Observations were made on intact plants of Eucalyptus calmudulensis, E. grandis, E. saligna and Quercus palustris using X-ray microtomography. We found no evidence of an effective xylem refilling mechanism in any of the plant species. Despite rehydration and recovery of plant water potential to near pre-drought levels, embolized vessels were not refilled up to 72 h after rewatering. In E. saligna, water droplets accumulated in previously air-filled vessels for a very small percentage of vessels. However, no instances of complete refilling that would restore embolized vessels to hydraulic function were observed. Our observations suggest that rapid refilling of embolized vessels after drought may not be a wide spread mechanism in woody plants and that embolism formed during drought represents long term cost to the plant hydraulic system.